Predictors of residual force enhancement in voluntary contractions of elbow flexors() - de Brito Fontana, Heiliane (J Sport Health Sci, 2018)
BACKGROUND: The steady-state increase in muscle force generating potential following a lengthening contraction is called residual force enhancement (RFE). In this study, we aimed to test for differences in torque, electromyographic activity (EMG), and the associated neuromuscular efficiency (NME) between isometric voluntary contractions of elbow flexors preceded and not preceded by a lengthening contraction. The dependence of such differences on (i) stretch amplitude, (ii) the region of the force–length (FxL) relationship where contraction occurs, and (iii) the individual's ability to produce (negative) work during the stretch was investigated. METHODS: Sixteen healthy adults participated in the study. Elbow flexor torque, angle, and biceps brachii EMG for purely isometric contractions (reference contractions) and for isometric contractions preceded by active stretches of 20° and 40° were measured at the ascending, plateau, and descending regions of subject-specific FxL curves. All contractions were performed in an isokinetic dynamometer. Two-factor (stretch × FxL region) repeated measures analysis of variance ANOVAs was used to analyze the effect of active stretch on EMG, torque, and NME across conditions. The relationships between mechanical work during stretch—calculated as the torque–angular displacement integral—and the changes in EMG, torque, and NME were analyzed using Pearson correlation. RESULTS: In general, torque, EMG, and NME following active stretches differed from the values observed for the purely isometric reference contractions. While although the detailed effects of active stretch on torque and EMG differed between regions of the FxL relationship, NME increased by about 19% for all muscle lengths. Up to 30% of the interindividual variability in torque generating potential change in response to active stretching was accounted for by differences in (negative) work capacity between subjects. CONCLUSION: Our results suggest that (i) RFE contributes to “flatten” the elbow flexor torque–angle relationship, favoring torque production at lengths where the purely isometric torques are reduced substantially, and (ii) RFE contributes to a reduction in energy cost of torque production during isometric contractions for the entire operating range.